Women Empowerment and Demand for Sexual and Reproductive Health Services - Francke, Pedro (2022)
We analyze the effect of women's empowerment on their demand for reproductive and sexual health services. In particular, we explore their use of modern contraceptive methods, if the women have had an HIV screening and if they have made a health consultation after experiencing symptoms of sexually transmitted infections. We calculate four women empowerment indexes, proxies to the economic dimension of empowerment, the freedom of movement to visit family or friends, the respect of their couple to their opinions, wishes and rights, and the ability of women to decide about their health. We found that freedom of movement for women at a medium level increases the probability of using modern contraceptive methods as well as screening for HIV/AIDS and that the couple's respect for the views and rights of women positively influences the use of modern contraceptive methods. However, women´s autonomy to make decisions regarding their health is the empowerment indicator with the most robust results on the use of sexual and reproductive health services, increasing the probability of using modern contraceptive methods and consulting for STI symptoms.